The effect of short-course high-dose methylprednisolone on peripheral blood CD34⁺ progenitor cells of children with acute leukemia during remission induction therapy - Tunç, Bahattin; Öner, Ahmet F.; Hiçsönmez, Gönül (The Turkish Journal of Pediatrics, 2002)
This study was undertaken to determine the effect of short-course high-dose methylprednisolone (HDMP) treatment on peripheral blood (PB) CD34⁺ progenitor cells during remission induction treatment in 11 children with newly diagnosed acute leukemia (7 with ALL, 4 with AML) whose bone marrow (BM) cells expressed fewer than 5% CD34 at the time of diagnosis. All children who had no infection were given HDMP as a single daily oral dose of 30 mg/kg for the first four days of induction therapy. The number of CD34⁺ progenitor cells were determined by flow cytometry before and after four days of HDMP treatment. While the number of PB blast cells significantly decreased after only a four-day course of HDMP treatment, the number of PB CD34⁺ progenitor cells increased in all patients. In addition, after four days of HDMP treatment polymorphonuclear leukocytes (PMN) and mononuclear cells (MNC) increased significantly (p < 0.05). We suggest that the potential beneficial effects of HDMP in the induction treatment of acute leukemia may occur partly by the stimulation of PB CD34⁺ hematopoietic progenitor cells in a short period of time.